How to unblock the financing of small and medium size farms in Romania? Financial instruments proposal for RDP 2014-2020 - Cornelia Mihai; Alexandra Toderiţă (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
Recent evidence shows that that over 60% of private investment contracts have been canceled due to the lack of private co-financing. Basically, a large part of the EU funds for agricultural development cannot be accessed due to the current poor access to finance of (small and medium-size) farmers. Several factors, such as guarantees of up to 150% of the loan value, low profitability, or high default risk that hinder the sector's access to the credit market, should be mitigated by state intervention. Such a measure can be included in the 2014-2020 RDP, consistent with the European Commission's recommendation to include financial instruments for supporting access to finance for farmers and agricultural associations. The analysis presented in this paper builds on the solutions proposed in a previous CRPE report focusing on microcredit, based on the existing mechanisms of the state. Firstly, it aims to support OUG 43/2013 by establishing: (1) a fund for middle-size farms for investment of up to 300,000 Euro, significantly lower than the previous ceiling of 3 mil. Euro and (2) a microcredit fund (max. 25,000 Euro), both measures coupled with an interest rate subsidy facility. Ultimately, the aim is to reduce the interest rate that farmers are facing by at least 4 percentage points. Secondly, we propose extending and improving the instruments designed for bearing part of the risk burden, through (1) a state aid scheme for reducing the cost of the guarantees for projects undertaken by young farmers and start-ups, and (2) providing 100% guarantee for young farmers that access RDP funds for agricultural investment.
Keywords: 330; agriculture; credit; guarantee; financial instrument; interest rate subsidy